Derivation in the Lamaholot Language, Tanah Boleng Dialect, Bayunta’a Village - Geroda, Marceline Clarista Perada; Djuli, Labu; Reteg, I Nyoman (LPPM Universitas Dhyana Pura, 2025)
This study aims to (1) investigate which word classes undergo derivational morphological processes in the Lamaholot language, Tanah Boleng dialect, Bayunta'a Village, and (2) describe the derivational morphological processes in the Lamaholot language, Tanah Boleng dialect, Bayunta'a Village. The method used is a morphological study. The research subjects are reliable informants. The research object is derivation in the Lamaholot language, Tanah Boleng dialect, Bayunta'a Village. The qualitative data analysis process is supported by qualitative descriptions using structured interviews. The results of this study revealled the following data obtained by the researcher. There are three types of affixes in the Lamaholot language: prefixes, suffixes, and infixes. There are three types of prefixes: (be-), (ke-), and (pe-). There is one type of suffix: (n-). There is one type of infix: (en-). There is also a change in the initial phoneme which is only found in verb derivation, namely the change from the basic word class of verb to noun (deverbal noun), which is (/D/>/K/), (/G/>/K/), (/H/>/N/), and (/T/>/N/).